EFEITOS DE UM ANÁLOGO À SUBSTÂNCIA APAZIGUADORA BOVINA SOBRE O CRESCIMENTO E ESTRESSE DE BEZERRAS DESMAMADAS - PIROTA, Giovana Gomes; VEDOVATTO, Marcelo; VIEIRA, Douglas Gomes; FERNANDES, Henrique Jorge (ANAIS DO ENIC, 2022)
-